Mesoscopic modeling impacts of liquid water saturation, and platinum distribution on gas transport resistances in a PEMFC catalyst layer. (20th August 2021) - Mu, Yu-Tong; Yang, Shu-Ran; He, Pu; Tao, Wen-Quan
Highlights: Local transport resistance in partially saturated electrode is numerically achieved. More Pt particles near gas diffusion layer are beneficial for resistance reduction. Oxygen diffusion coefficient in wet electrode decreases with the contact angle. Contribution of ionomer dominates the electrode resistance at low platinum loading. Abstract: The oxygen transport resistance in catalyst layer of proton-exchange-membrane fuel cells has garnered much attention because it increases dramatically with the decreasing platinum loading. In this paper, the local transport behaviors of oxygen in electrode with different liquid water saturations, and platinum distributions are explored at mesoscopic level. The two-phase flow regime in electrode is simulated via a multicomponent multiphase flow model to reconstruct the liquid water morphologies. The effective oxygen diffusivities under wet conditions, the limiting current density, and the electrode resistance are numerically obtained before determining the local transport resistance. The results demonstrate that the effective oxygen diffusivities under wet condition decrease with the contact angle of the electrode. The limiting current density decreases with the liquid water saturation due to the blockage of ionomer surface area and the decreasing pore size distribution. The contribution of ionomer and liquid water to the electrode resistance dominates for the electrode resistance at low platinum loading. The local transport resistance of hydrophilic electrodes increases dramatically if the oxygen permeation in liquid water is excluded. More platinum particles distributed near the gas diffusion layer are beneficial for the reduction of the local transport resistance.